Multiple Representation Strategy through Team-Based Representational Activities with Creative Exploration via Learning through Video on Cell Fundamentals - Ahmar, Dewi Satria; Azzajjad, Muhammad Fath (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
In the era of digitalized science education, students’ ability to construct, connect, and communicate scientific ideas through multiple representations is increasingly vital. This study examined the effectiveness of a Multiple Representation Strategy via Team-Based Representational Activities with Creative Exploration through Learning via Video in improving representational abilities on cell fundamentals. The research involved 20 undergraduate students from a 2019 Chemistry Education cohort. Using a Project-Based Learning (PJBL) model, students collaboratively produced educational videos based on lecture subtopics. Representational ability was assessed through five essay items aligned with indicators: verbal, visual, symbolic, integrated, and creative. Descriptive results showed verbal representation scored highest (M=84), followed by visual (M=78), while symbolic (M=65) and integrated (M=68) scored lowest. Regression analysis revealed verbal, visual, and integrated representations significantly predicted overall performance (p < 0.05), with verbal being the strongest predictor (β = 0.421). These findings suggest that the PJBL-video approach supports expressive and visual learning well but needs enhancement in fostering symbolic and integrative skills. The study highlights the importance of instructional strategies that encourage communication, creativity, and abstract reasoning. Insights from this research can inform the development of science pedagogy and curriculum aimed at improving representational fluency, especially in biochemistry education and broader STEM learning contexts.